Niqab and Religious Identity: The Perspectives and Motives of Niqab Utilization among Female Students in UNKAFA, Gresik - Yahya , Mokhammad; Rosi, Rois Imron; Imamuddin; Fadil (Religia: Jurnal Ilmu-Ilmu KeIslaman, 2025)
The use of niqab in educational realm consistently evokes controversy and leads to ongoing debates nationally and internationally. Furthermore, the use of niqab in educational settings can lead to the possible emergence of the negative stereotype and stigma. Several previous studies concluded that understanding the motives and perspective behind the niqab use is crucial for minimizing the appearance of such stigma. This study holds significant interest as it will involve in-depth exploration of the niqabi student’s perspectives, examining their motives and the formation of their religious identity within this specific institutional context. Using qualitative research method, this study explored 20 female students from UNKAFA, Gresik. The result of study revealed that among UNKAFA female students, there are two primary religious perspectives on niqab: permissible and Sunnah. Regarding the meaning of the niqab among these students, at least five primary interpretations emerged: submissive attitude toward the university, religious expression, manifestation of self-identity, tool for enhancing confidence, and fashion expression. Concerning the motives, there are at least two main types those are social and individual motives. This research also concludes that the majority of informants stated that the niqab is not a manifestation of their religious identity, but it is merely a submissive attitude toward campus policy. The finding also indicated that textual practices mediated by an appropriate authority are capable of vitalizing Qur’anic values and reinforcing the effort toward the living qur’an within student’s daily lives at pesantren-based university. This study academically contributes to enriching the specific practice of living qur’an inside pesantren-based university, individual religious perspectives, motives, and multifaceted meanings attributed to the niqab and highlights the complex interplay of social influences, personal beliefs, and construction of religious identity.